Down by the riverside: urban riparian ecology. Issue 6 (1st August 2003) - Groffman, Peter M.; Bain, Daniel J.; Band, Lawrence E.; Belt, Kenneth T.; Brush, Grace S.; Grove, J Morgan; Pouyat, Richard V.; Yesilonis, Ian C.; Zipperer, Wayne C.
Abstract : Riparian areas are hotspots of interactions between plants, soil, water, microbes, and people. While urban land use change has been shown to have dramatic effects on watershed hydrology, there has been surprisingly little analysis of its effects on riparian areas. Here we examine the ecology of urban riparian zones, focusing on work done in the Baltimore Ecosystem Study, a component of the US National Science Foundation's Long Term Ecological Research network. Research in the Baltimore study has addressed how changes in hydrology associated with urbanization create riparian "hydrologic drought" by lowering water tables, which in turn alters soil, vegetation, and microbial processes. We analyze the nature of past and current human interactions with riparian ecosystems, and review other urban ecosystem studies to show how our observations mirror those in other cities.